Role of media in shaping the policy process: Comparative lessons from the food price crisis in Bangladesh, China, India, and Viet Nam - Babu, Suresh Chandra; Aggarwal, Smita; Chen, Junjie (International Food Policy Research Institute, 2017)
News media not only inform the public about policy changes but also help to build public opinion with a serious potential to influence the policy-making process, especially during times of crisis or an emergency. During the global food price crisis of 2008, international and domestic press reported extensively on the crisis in the form of news reports, analyses, expert opinions, and interviews with key stakeholders. In this discussion paper, we compare media coverage by news publications in four developing countries—Bangladesh, China, India, and Viet Nam—and explore its linkages with policy responses. Our discussion focuses on the role of media in the emergency policy-making process in selected countries during the time of the global food crisis from 2008 to 2012. Through this paper, we attempt to connect the media’s role with empirical evidence from daily newspapers in study countries and the timing of policy making during the ensuing years of food price crisis. We draw comparative lessons from the role media played in stabilizing food prices. Political systems in the country, it is argued, determine the extent to which media can influence policy making; identify policy problems and stakeholders during crisis; provide policy options to policy makers; and play the role of a policy evaluator. Our discussion may be useful for international and national policy-making bodies to understand media coverage during the crisis as well as inform media practitioners as to how their counterparts in different countries covered the crisis.